Preparation of Copper-coated Polyester Fabric via Electroless Plating Using Glyoxylic Acid as Reducing Agent (Journal of Fiber Bioengineering and Informatics, 2015)
An environmental-friendly electroless copper plating process was employed in preparing copper-coated\rpolyester fabric with excellent conductivity. The effects of bath temperature on the plating rate,\rcompositions and crystal structure of the electroless copper deposits were studied. The results showed\rthe deposition rate increased with the rise of the bath temperature. X-ray Diffraction (XRD) scan\rindicated that the copper coating deposited was well crystallized and Scanning Electron Microscopy\r(SEM) scan showed copper coating had good surface morphology. Surface resistance of copper plated\rpolyester fabric was evaluated. The surface resistance was 16.5 m\u03a9/sq as the temperatue was 65 \u00a0\u00baC.
Keywords: Glyoxalic Acid; Electroless Copper; Polyester Fabric; Surface Resistance; Bath Temperature